Working in the hidden economy: Associations with the latent benefits and psychological health - Šverko, Branimir (Array, 2008)
Hidden economy working can provide income and cushion the financial hardship during unemployment. But, can it also substitute for some latent functions of regular employment? According to Jahoda's theory, the latent functions include the time structure, regular shared experience, information about personal identity, a link with the collective purpose, and enforced regular activity. This paper explores whether the undeclared working reduces the degree of deprivation of these functions during unemployment and, consequently, improves the psychological health of a person. The data were collected from a sample of unemployed persons (N = 1138) registered with the Croatian Employment Bureau. A series of questions about their day-to-day activities were used to estimate the amount of undeclared working, an ad hoc developed scale to assess the extent of their latent deprivation, and the SF-36 Health Survey to measure their psychological health. The ANCOVA revealed that the participants who were often engaged in the hidden economy working exhibited reduced latent deprivation and improved psychological health compared to those who were sometimes engaged. Hierarchical regression analysis indicated that their better psychological health was partially mediated through reduced latent deprivation. However, the unemployed who were never engaged in undeclared working exhibited a relatively high psychological health as well.